Pushing the thinness limit of silver films for flexible optoelectronic devices via ion-beam thinning-back process - Dongxu Ma; Ming Ji; Hongbo Yi; Qingyu Wang; Fu Fan; Bo Feng; Mengjie Zheng; Yiqin Chen; Huigao Duan (Nature Communications, 2024)
Abstract Reducing the silver film to 10 nm theoretically allows higher transparency but in practice leads to degraded transparency and electrical conductivity because the ultrathin film tends to be discontinuous. Herein, we developed a thinning-back process to address this dilemma, in which silver film is first deposited to a larger thickness with high continuity and then thinned back to a reduced thickness with an ultrasmooth surface, both implemented by a flood ion beam. Contributed by the shallow implantation of silver atoms into the substrate during deposition, the thinness of silver films down to 4.5 nm can be obtained, thinner than ever before. The atomic-level surface smooth permits excellent visible transparency, electrical conductivity, and the lowest haze among all existing transparent conductors. Moreover, the ultrathin silver film exhibits the unique robustness of mechanical flexibility. Therefore, the ion-beam thinning-back process presents a promising solution towards the excellent transparent conductor for flexible optoelectronic devices.